Modeling Risk Management for Resources and Environment in China - Wu, Desheng Dash.; Zhou, Yong.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This edited volume expands the scope of risk management beyond finance to include resources and environment issues in China. It presents the state-of-the-art approaches of using risk management to effectively manage resources and environment. Both case studies and theoretical methodologies are discussed.
Keywords: Economics; Environmental economics; Operations research; Economics/Management Science; Operation Research/Decision Theory; Environmental Economics